Design of radiation-hard CMOS sensors for particle detection applications : doctoral thesis - Berdalović, Ivan; Suligaj, Tomislav (Zagreb : I. Berdalović; Fakultet elektrotehnike i računarstva, 2019)
The work focuses on the design of large-scale radiation-hard monolithic CMOS sensors for the upgrades of the detectors in the high-energy physics experiments at CERN. The sensors are manufactured using a novel process modification implemented in the TowerJazz 180 nm CMOS process, which uses small collection electrodes to achieve a low sensor capacitance in the order of a few femtofarads, resulting in low noise and low analogue power consumption. The process modification provides full depletion of the sensitive layer and a radiation hardness promising to meet the requirements of the pixel detectors in CERN’s largest experiments. The sensors implement a matrix of small pixels (in the order of 30 micrometres) containing a fast, low-noise front-end amplifier and a novel asynchronous digital readout architecture. Measurement results from these sensors before and after irradiation are also discussed.
Keywords: Active pixel sensors, CMOS integrated circuits, position sensitive particle detectors, radiation effects, radiation hardening (electronics), semiconductor detectors, solid-state circuit design.
Rad se bavi projektiranjem monolitnih CMOS senzora otpornih na zračenje za primjenu u detektorima u eksperimentima fizike elementarnih čestica u CERN-u. Senzori su proizvedeni u novoj modifikaciji standardnog TowerJazz 180 nm CMOS procesa te koriste male sakupljačke elektrode kako bi se postigao mali kapacitet reda veličine nekoliko femtofarada, što omogućuje niske razine šuma i nisku analognu disipaciju snage. Modifikacija procesa omogućuje potpuno osiromašenje sloja za detekciju i time otpornost na zračenje koja može ispuniti zahtjeve piksel detektora u najvećim CERN-ovim eksperimentima. Senzori sadrže matricu malih piksela (reda veličine 30 mikrometara) koji osim sakupljačke elektrode sadrže brzo niskošumno pojačalo i novu asinkronu digitalnu logiku za očitavanje podataka iz piksela. Rad će također predstaviti rezultate mjerenja na proizvedenim sklopovima prije i poslije zračenja.
Ključne riječi: Aktivni piksel senzori, CMOS integrirani sklopovi, detektori čestica osjetljivi na položaj, efekti zračenja, otpornost (elektronike) na zračenje, poluvodički detektori, projektiranje poluvodičkih sklopova.
Bibliografija str. 109-116.